PENGARUH PERAN GURU PPKn TERHADAP KECERDASAN MORAL SISWA DI SMA NEGERI 1 CERENTI KABUPATEN KUANTAN SINGINGI - Jeni Saputra; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by the role of PPKn teachers at SMA Negeri 1 Cerenti, Kuantan Singingi Regency. The formulation of the problem in this study is whether there is an influence of the role of the Civics teacher on the moral intelligence of students at SMA Negeri 1 Cerenti, Kuantan Singingi Regency. The purpose of the study was to determine whether there was an influence of the role of the Civics teacher on the moral intelligence of students at SMA Negeri 1 Cerenti, Kuantan Singingi Regency. The benefits of research, hopefully with this research the authors hope that it can help become a source of knowledge and contribute to the world of education related to writing scientific papers about the role of teachers on the moral intelligence of students in schools. This research method is descriptive quantitative, data collection instrument using a questionnaire consisting of 16 question. The population in this study were students of SMA Negeri 1 Cerenti, Kuantan Singingi Regency, amounting to 700 people consisting of class X, XI and XII, with a sample of 15% of the total population to 106 respondents using the Proportional Sampling Technique. Based on the results of the study, there is a positive influence between the role of Civics teachers on students' moral intelligence. This can be proven by a simple linear regression analysis using the SPSS application, namely = 4.727 + 0.608 X. The results of the above equation can be translated as a constant of 4.727 which means that the value of the consistency of the PPKn teacher's role is 4.727, the regression coefficient of X is 0.608 which states that the addition of 1 % of the value of the role of PPKn teachers, the students' moral intelligence will increase by 0.608. This coefficient is positive, meaning that the role of PPKn teachers (X) on students' moral intelligence (Y) has a positive effectKey Words : Influence, The Role of PPKn Teachers, Moral Intelligence